2008
DOI: 10.1108/14637150810903066
|View full text |Cite
|
Sign up to set email alerts
|

Process management tasks: a conceptual and practical view

Abstract: Purpose -The purpose of this paper is to contribute to defining the tasks necessary to process management, considering both conceptual and practical views. Design/methodology/approach -Bibliographic review for tasks mentioned as typically necessary to process management, plus a field survey involving professionals working in process management. Findings -The bibliographic review yielded a set of tasks that were grouped conceptually into "designing processes", "managing processes from day to day" and "fostering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
0
46

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(186 citation statements)
references
References 26 publications
(19 reference statements)
4
136
0
46
Order By: Relevance
“…In addition, the quality knowledge is important to accelerate the transition progress from functional to process-based management for certified organization. This is due to the fact that despite the importance of process-based management, the transition of the organization of a functional approach to an approach focused on processes still happens slowly as suggested by Neubauer (2009), Paim et al (2008) and McCormack et al (2009). Taken together, this result suggests that organization shall put necessary strategy and effort to ensure that the quality knowledge is used for all processes and its interactions.…”
Section: Analysis Of the Structural Model (Second-order)mentioning
confidence: 89%
“…In addition, the quality knowledge is important to accelerate the transition progress from functional to process-based management for certified organization. This is due to the fact that despite the importance of process-based management, the transition of the organization of a functional approach to an approach focused on processes still happens slowly as suggested by Neubauer (2009), Paim et al (2008) and McCormack et al (2009). Taken together, this result suggests that organization shall put necessary strategy and effort to ensure that the quality knowledge is used for all processes and its interactions.…”
Section: Analysis Of the Structural Model (Second-order)mentioning
confidence: 89%
“…Na abordagem conhecida como gestão funcional a organização tem característica de silos com baixa capacidade de coordenação e baixa orientação a mercado (PAIM et al, 2008). O BPM não elimina as unidades funcionais, mas adota uma perspectiva horizontal para elas, dando prioridade à estruturação do fluxo de trabalho de ponta a ponta da organização, com ênfase nos interesses do cliente (PAIM et al, 2008).…”
Section: Business Process Management (Bpm)unclassified
“…Por fim, uma breve reflexão sobre o trabalho e sugestão de pesquisa futura. (RODRIGUEZ, 2010). Porém, Rodriguez (2010) afirma que a existência de um modelo é necessária para o adequado funcionamento empresarial, sendo a forma, estruturada e organizada, como ocorre a integração entre os sistemas internos e assegura o atendimento às estratégicas do negócio.…”
Section: Introductionunclassified
“…While process owners are considered responsible for managing processes little is known about what they are supposed to do beyond assuming responsibility for (a) process performance and (b) process improvement (Reijers & Peeters, 2010) In the absence of a specific process owner task framework general BPM tasks may be applicable to the process owner role. A literature review, for instance, found three categories of BPM tasks which bear relationship to process owners: designing processes; day-to-day management of processes; and fostering process related learning (Paim, Mansur Caulliraux, & Cardoso, 2008). However, this postulation is not supported empirically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Armistead (1996) provided ten principles of managing business processes: (i) designate a process champion; (ii) know the process (iii) understand the linkages; (iv) work on the trade-offs; (v) teach others about the process; (vi) train within the process; (vii) measure the process; (viii) manage careers; (ix) build specialist expertise; and (x) improve the process. Three groups of tasks have been suggested: designing processes, day-to-day process management; and nurturing process related learning (Paim et al, 2008). Over time technology has become more relevant while interpersonal skills have become vital (Scholtz et al, 2011).…”
Section: Summary Of Tasks and Competenciesmentioning
confidence: 99%